2023
DOI: 10.1590/2177-6709.28.1.e23spe1
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea: a review for the orthodontist

Abstract: Introduction: Obstructive sleep apnea (OSA) affects an important part of the population and is characterized by recurrent total or partial obstruction of the upper airway (UA) during sleep, negatively affecting the quality of life of patients in the short and long terms, and constituting an important public health problem for the society. The field of expertise of orthodontists is closely related to the UA, placing them in a strategic position to diagnose air passage failures and intervene when necessary. Orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Cone-beam computed tomography (CBCT) represents a widely used oral and maxillofacial diagnostic tool that provides a three-dimensional view of the hard- and soft-tissue structures of the head and neck [ 26 ], which is capable of acquiring quality images that are useful in the analysis and diagnosis of the upper airways. Evaluating the upper airways’ volume in OSA patients is mandatory because it has been demonstrated that these patients have a reduced upper airway volume.…”
Section: Discussion Review Of Findingsmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) represents a widely used oral and maxillofacial diagnostic tool that provides a three-dimensional view of the hard- and soft-tissue structures of the head and neck [ 26 ], which is capable of acquiring quality images that are useful in the analysis and diagnosis of the upper airways. Evaluating the upper airways’ volume in OSA patients is mandatory because it has been demonstrated that these patients have a reduced upper airway volume.…”
Section: Discussion Review Of Findingsmentioning
confidence: 99%
“…Obstructive sleep apnea syndrome (OSA) is a sleep disorder that has a high prevalence in the world population; it is characterized by a partial or total collapse of the upper airways (UAs) during sleep due to recurrent episodes of apnea or hypopnea [1]. The recovery of regular breathing after this type of episode occurs with respiratory effort, leading to sleep fragmentation, decreased sleep quality, and daytime sleepiness [2].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of people affected by OSA varies between 14% and 84% in men and from 5% to 61% in women. However, it is thought that the number is undervalued and that many more people with OSA do not have a definitive diagnosis [2,3] According to international recommendations, the diagnosis of OSA is performed through a sleep examination, namely a polysomnography (PSG) or home sleep apnea testing (HSAT) [4]. Apnea is defined as a 90% reduction in airflow lasting at least 10 s. Hypopnea is defined as a decrease in airflow of at least 50% and a decrease in oxygen saturation of 3% for at least 10 s. However, accredited sleep centers are allowed to classify hypopneas when there is an oxygen desaturation ≥4% of pre-event baseline, in adults.…”
Section: Introductionmentioning
confidence: 99%